Pengaruh Pembelajaran Daring Terhadap Literasi Numerasi - Ignasius Henio Altoris; Muhammad Yunus; Fathimah Az.Zahra Nasiruddin (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This research aims to determine the effect of online learning on the numeracy literacy of eighth-grade students in SMP Negeri 35 Makassar. This type of research is ex post facto research with a quantitative approach. The research sample is 120 students of eighth-grade students. Data collection techniques used were questionnaires and test questions. The results showed that based on four indicators in online learning, namely, online learning during a pandemic, online learning processes, online learning effectiveness, and online learning supporting factors, the average value of online learning indicators was 65, 5%, proven to affect the numeracy literacy of eighth-grade students in SMP Negeri 35 Makassar includes four hands namely, numbers, operations and calculations, geometry and measurement, and mathematical data processing with the magnitude is 5.9%. The study results based on a simple regression test obtained a significance value of 0.007 <0.05. Thus, it can be concluded that online learning affects the numeracy literacy of eighth-grade students in SMP Negeri 35 Makassar.